Dynamic positioning base station for wireless sensor network using particle swarm optimization (PSO) - Nurul Adilah Abdul Latiff (Universiti Malaysia Perlis, 2012)
The positioning of base station is one of the methods to improve the overall performance of wireless sensor network. The base station is normally located far from the sensing area. Therefore, all sensor nodes use extra power to transmit its data to this far base station and result in higher energy consumption. In some situations, the base station can be placed in the middle of a sensing area. However in this case, a sensor node that is located at the edge of the sensing area consumes more energy to transmit data to the base station compared to sensor nodes that are located near the base station. This creates unbalanced energy consumption among all sensor nodes and furthermore reduces the network energy efficiency. Since the optimal selection of base station location in a network belongs to nondeterministic polynomial (NP) hard problem, the use of approximation algorithms such as Particle Swarm Optimization (PSO) are generally more suitable due to its simplicity and outstanding search strength.